Penentuan Lokasi Pada Perencanaan dan Perancangan Digital Art Gallery Di Denpasar: Bahasa Indonesia - I Putu Aldiana Pebrian; I Kadek Merta Wijaya; Gde Bagus Andhika Wicaksana (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
The development in Indonesia seen from the last few years, art Digital has begun to be known and popular among professional artists. Bali As an island or destination of world tourism, seen from tourism withits traditions and culture . In the era of rapid globalization, the art world began Evolving with the advent of digital art that is in the process of making and The final presentation uses computer technology. Digital art artists in Denpasar, which is still underappreciated by the general public, needs to there are efforts to increase tourism in Denpasar through providing Facilities for artists Digital Art artists are one of the solutions whereIt is expected to improve the quality of digital art and the publicVisiting can appreciate the work of artists so that later digital art will be more Widely known and young artists are more eager to work. With Observation method, is the stage of data collection carried out by surveying the location of libraries or similar objects to obtain More in-depth and real information about the design object